Economic feasibility of small-scale rubber plantations in Assam - Maibangsa M; Subramanian S R (Journal of Rubber Research, 2000)
This study attempts to examine the cost structure and economic feasibility of small-scale rubber plantations in Assam. The total cost for establishing one hectare of rubber holding was estimated at US$ 1233.40. During the tapping period, maintenance cost required was US$ 390 per hectare per annum. The total cost of production of rubber was US$ 592.40 per hectare per annum. Labour, manure and fertilisers were found to be the dominant items of cost. In spite of the high cost of production, small-scale rubber cultivation in Assam is a highly remunerative enterprise with a net return of US$ 637 per hectare per annum. It was also found to be economically viable and cost effective as indicated by satisfactory values of net present worth (US$ 1101.50), benefit-cost ratio (1.71) and modified internal rate of returns (17.58;).
Keywords: Economic feasibility; Rubber plantations